DNA polymerase β deficiency is linked to aggressive breast cancer: A comprehensive analysis of gene copy number, mRNA and protein expression in multiple cohorts. Issue 3 (10th January 2014) - Abdel-Fatah, Tarek M.A.; Russell, Roslin; Agarwal, Devika; Moseley, Paul; Abayomi, Michael Ayotunde; Perry, Christina; Albarakati, Nada; Ball, Graham; Chan, Stephen; Caldas, Carlos; Ellis, Ian O.; Madhusudan, Srinivasan
Abstract : Short arm of chromosome 8 is a hot spot for chromosomal breaks, losses and amplifications in breast cancer. Although such genetic changes may have phenotypic consequences, the identity of candidate gene(s) remains to be clearly defined. Pol β gene is localized to chromosome 8p12‐p11 and encodes a key DNA base excision repair protein. Pol β may be a tumour suppressor and involved in breast cancer pathogenesis. We conducted the first and the largest study to comprehensively evaluate pol β in breast cancer. We investigated pol β gene copy number changes in two cohorts (n = 128 & n = 1952), pol β mRNA expression in two cohorts (n = 249 & n = 1952) and pol β protein expression in two cohorts (n = 1406 & n = 252). Artificial neural network analysis for pol β interacting genes was performed in 249 tumours. For mechanistic insights, pol β gene copy number changes, mRNA and protein levels were investigated together in 128 tumours and validated in 1952 tumours. Low pol β mRNA expression as well as low pol β protein expression was associated high grade, lymph node positivity, pleomorphism, triple negative, basal‐like phenotypes and poor survival (ps < 0.001). In oestrogen receptor (ER) positive sub‐group that received tamoxifen, low pol β protein remains associated with aggressive phenotype and poor survival (ps < 0.001). Artificial neural network analysis revealed ER as a top pol β interacting gene. Mechanistically, there was strong positive correlation between pol β gene copy number changes and pol β mRNA expression (p < 0.0000001) and between pol β mRNA and pol β protein expression (p < 0.0000001). This is the first study to provide evidence that pol β deficiency is linked to aggressive breast cancer and may have prognostic and predictive significance in patients. Highlights: Pol β is a key base excision repair protein and may be involved in breast cancer. Pol β gene, mRNA, and protein expression was investigated in large cohorts. Pol β deficiency is associated with aggressive breast cancer and poor prognosis. Pol β deficiency predicts response to endocrine therapy.